Turks, Moors and Englishmen in the Age of Discovery - Nancy L. Stockdale (International Institute of Islamic Thought, 2001)
Nabil Matar's Turks, Moors and Englishmen in the Age of Discovery is a welcome addition to the important yet often-overlooked scholarship of cross-cultural exchanges between Muslims and non-Muslims in the era between the Crusades and modem European colonial hegemony. Drawing on literary and historical sources from the Elizabethan and Stuart periods, Matar strikes at the heart of the Orientalism debate with a complicated yet plausible link between English representations of Muslims and native Americans and later imperialist racism. By stressing a triangular power relationship between England, North Africa and the Ottoman world, and the new American colonies, Matar convincingly argues that it was the very failure of the English to conquer the Muslims in the face of English successes in America against the indigenous populations that led Britons to transfer their ideas about "savage natives" from the American Indians to the Muslims. According to Matar, it was this transference that laid the foundation for centuries of racism and stereotyping against Islam and its adherents in western scholarship and popular culture. By using the language of racism created during their destruction of the native Americans against the Muslims they could not destroy, the English in the Age of Discovery created the ideological foundation for their conquests in the Age of Imperialism. In his introduction, Matar is quick to remind his readers that Muslims were the most familiar and significant Others in Elizabethan and Stuart England unlike Americans, they were not in the colonial sights of the English, but rather, to be admired and feared. Indeed, it was their very resistance to being conquered that led to their demonization in literary and theological works. However, in the realm of politics, English rulers were keen to forge political and economic ties with Muslim governments, because they knew they needed such ties to maintain their own national and economic security. Matar is also careful to point out that English representations of Muslims cannot be taken at face value as accurate historical sources describing lived experiences of Muslims, but rather, as representations of how the English viewed the Islamic world they knew vis-a-vis the other major group of non-Christians with which they were actively engaged, Native Americans. The bulk of Matar's work can be divided into two parts. Chapter One ...